Art After Syariat: Sebuah Konsep Seni Rupa dalam Perspektif Syariat Agama Islam - Abiyoga, Taufan Amirullah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to describe the boundaries of fine art according to Islamic religious law which gives birth to artistic concepts according to Islamic religious guidelines. The methodology used is a descriptive qualitative method with a literature study approach with data sources in the form of books, research journals, the Koran, hadith books and ulama fatwas. The data analysis technique uses interactive model analysis. The results of the study from several literary sources are a new concept in fine arts that is in accordance with the review of Islamic religious law, namely art after sharia, thus triggering the creativity of artists in creating fine arts in accordance with Islamic law.